1982
DOI: 10.22237/elephant/1521731887
|View full text |Cite
|
Sign up to set email alerts
|

On the Dissection of a Female Asian Elephant (Elephas maximus maxiums Linnaeus, 1758) and Data from Other Elephants

Abstract: This elephantine project would have been virtually impossible without the tremendous help received from the Ringling Bros. and Barnum & Bailey Circus, various departments within Wayne State University, the numerous individuals involved, and the anonymous donors. The officials and other individuals at the Ringling Bros. and Barnum & Bailey Circus (Irvin and Kenneth Feld, Daniel C. Laughlin, Franz Tisch, Jim "Chico" Williams) were generous, very understanding and accommodating. With regard to the departments wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…This finding is interesting insofar as the elephant also displays surprisingly short ingesta retentions times for its BM , which could be explained, amongst other factors, by a comparatively short GIT (Shoshani et al 1982;Clauss et al 2003) and a decreased GIT capacity. Clauss et al (2003) explained that existing data, though scarce, particularly indicated the possibility that elephants have a comparatively small caecum.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This finding is interesting insofar as the elephant also displays surprisingly short ingesta retentions times for its BM , which could be explained, amongst other factors, by a comparatively short GIT (Shoshani et al 1982;Clauss et al 2003) and a decreased GIT capacity. Clauss et al (2003) explained that existing data, though scarce, particularly indicated the possibility that elephants have a comparatively small caecum.…”
Section: Introductionmentioning
confidence: 83%
“…In combination with the particularly short length of the GIT of elephants (Shoshani et al 1982;Clauss et al 2003), this finding gives rise to the question as to what factors determine the remarkable uniformity of the BM-GIT capacity relationship among mammals (and possibly other species). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Skin samples were obtained from three extant elephants: Elephas maximus (Asian elephant, EL 1, 14 years old) (Shoshani et al, 1982), Loxodonta africana (African elephant, EL 4, 2 years old) (Shoshani, unpublished data), and a putative intergeneric hybrid elephant (EL 3, 16 years old) between a male African elephant and a female Asian elephant (Lowenstein and Shoshani, 1996). A muscle specimen (EL 5) collected from the same Asian elephant specimen (EL 1) was included for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Shoshani et al (1982) tabulated the bones and their numbers for one Asian elephant and noted some of the differences between the two elephant species. Below is a summary of the number of bones for Ahmed.…”
Section: Number Of Bonesmentioning
confidence: 99%
“…If we add to this number additional bones that may have been present in Ahmed's skeleton, we get this new total: 280 subtotal from previous total + 1 interparietal cone (found in the cranium; according to Shoshani et al, 1982:43, the interparietal is absent in elephants, but according to Mariappa, 1986:4-5 this bone is present in the Asian elephant) + 9 turbinals (bones associated with the sense of smell) + 2 acetabuli (found in the acetabular fossae of the pelves, delineated in fetuses or newly born) + 2 centralia (bones in the forefeet, in most cases they are fused to the os magnum) + 40 sesamoid bones [found in the manus ("hands"), and pedes ("feet"); in old elephants, however, two bones on each "finger" may be ___ fused, some may be missing].…”
mentioning
confidence: 99%